PENGARUH PEMANFAATAN MEDIA TIGA DIMENSI BERBASIS POWERPOINT TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV UPT SPF SD INPRES MALENGKERI I - Nurmuzdalifah; Haerul Syam; Andi Alim Syahri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using PowerPoint-based three-dimensional media on the mathematics learning outcomes of fourth-grade students at UPT SPF SD Inpres Malengkeri I. This research employs a pre-experimental design, specifically the one-group pretest-posttest design. The research subjects consisted of all 18 fourth-grade students. Data were collected through pretest and posttest assessments and subsequently analyzed using descriptive and inferential statistics. The results indicate that the average score increased from 45.72 on the pretest to 94.22 on the posttest. The N-Gain score of 0.8946 falls into the high category. Furthermore, hypothesis testing results demonstrate that the use of PowerPoint-based three-dimensional media has a significant effect on students' mathematics learning outcomes. Thus, PowerPoint-based three-dimensional media is effective for mathematics instruction—particularly regarding the topic of geometric solids—as it helps students grasp concepts in a more concrete, engaging, and enjoyable manner.